GREEN PRODUCTIVITY ANALYSIS BASED ON ENVIRONMENTAL RISK ANALYSIS AND ENVIRONMENTAL PERFORMANCE IN THE LIQUID WASTE ASPECT OF PT NATA DE COCO X - Andini Nur Anisa B; Nabila Putriyandri Alifa; Sillak Hasiany (Bulletin of Engineering Science, Technology and Industry, 2026)
The food and beverage industry, including Nata de Coco production in Indonesia, plays a vital role in the economy. PT Nata de Coco X, as a market leader in this sector, needs to implement the Green Productivity concept to meet green industry standards. This study aims to evaluate the implementation of Green Productivity based on environmental risk and performance analysis. Considering that the liquid waste discharge almost exceeds the established quality standards, the environmental risk is indicated as high. Data triangulation methods (questionnaires, observations, and interviews) indicate that out of 16 processes, 6 are classified as low, 9 are classified as moderate, and 1 is classified as medium in the qualitative environmental risk analysis. The semi-quantitative method produces an overall environmental risk score of 102, which is classified as low risk. The environmental performance assessment shows a score of 94.4, categorized as very good. These findings are reinforced by observations and interviews. A Green Productivity strategy was developed using cause-and-effect analysis and a fishbone diagram, with 11 main strategies identified. The 5W1H analysis is used to develop a strategy, resulting in 1 first priority solution, namely utilizing wastewater from washing packaging, ablution and washing vegetables for watering plants, the last priority solution is installing pipes/hoses as a suitable wastewater drainage path.